2020
DOI: 10.3390/cancers12092608
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of MicroRNAs in Thyroid Cancers—A Systematic Review and Meta-Analysis

Abstract: Thyroid cancer (TC) includes various phenotypes, from indolent to highly aggressive cancer. The limitations of the current prognostication systems to predict the recurrence risk and the variability in expression of the genes involved in the thyroid carcinogenesis uncover the need for new prognostic biomarkers by taking into account potential epigenetic differences. We aimed to summarize the current knowledge regarding the prognostic impact of microRNAs (miRNAs) in TC. A literature search was conducted in PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 101 publications
(388 reference statements)
0
11
0
Order By: Relevance
“…Recently, cutting-edge studies have certified miRNA was related to tumorigenesis and progression and could be considered as a potential biomarker in diagnosis, recurrence, treatment and prognosis of tumors. According to previous reports, miRNA was associated with diagnosis, prognosis, recurrence and therapy in breast cancer and papillary thyroid carcinoma [25][26][27][28], prognosis and therapy in ovarian cancer and colorectal cancer [29,30], diagnosis and progression in pancreatic cancer [31], prognosis in hepatocellular carcinoma and lung cancer [32,33]. As far as endometrial cancer, we listed several reports as following: Multivariate analysis demonstrated the decreased expression of miRNA-152 and miRNA-101 lead to poor prognosis in endometrial serous adenocarcinomas [32].…”
Section: Discussionmentioning
confidence: 94%
“…Recently, cutting-edge studies have certified miRNA was related to tumorigenesis and progression and could be considered as a potential biomarker in diagnosis, recurrence, treatment and prognosis of tumors. According to previous reports, miRNA was associated with diagnosis, prognosis, recurrence and therapy in breast cancer and papillary thyroid carcinoma [25][26][27][28], prognosis and therapy in ovarian cancer and colorectal cancer [29,30], diagnosis and progression in pancreatic cancer [31], prognosis in hepatocellular carcinoma and lung cancer [32,33]. As far as endometrial cancer, we listed several reports as following: Multivariate analysis demonstrated the decreased expression of miRNA-152 and miRNA-101 lead to poor prognosis in endometrial serous adenocarcinomas [32].…”
Section: Discussionmentioning
confidence: 94%
“…The high expression of four miRs (miR-146a, miR-146b, miR-182, and miR-203) and the low expression of six miRs (miR-1271, miR-791, miR-381, miR-let 7a, miR-26a, miR-486) was correlated with decreased OS in PTC [ 61 ]. We did not get significant correlations of miR-222, -221, -146b, -181b, -21 with OS in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of these 3 miRs panel was associated with decreased OS. Interestingly, overexpression of miR-146b [ 61 ], miR-21 [ 23 ] were found to be associated with shorter disease-free survival in PTC patients. Since these miRs have interfaces with disease free survival and OS their expression may be important in predicting the course of PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2015 American Thyroid Association (ATA) guidelines proposed a three-tiered (high, intermediate, and low-risk) stratification [6]. This system considers the TNM staging, the surgical information, as well as the molecular data, whenever available [8][9][10].…”
Section: Introductionmentioning
confidence: 99%